2021
DOI: 10.1097/md.0000000000028218
|View full text |Cite
|
Sign up to set email alerts
|

Long-acting versus short-acting granulocyte colony-stimulating factors among cancer patients after chemotherapy in China

Abstract: Background: Granulocyte colony-stimulating factors (G-CSFs) include long-acting ones and short-acting ones. They have been mainly applied in Chinese clinical practice for years to prevent neutropenia. However, which type of G-CSF is more superior has not been conclusively determined. Methods: A systematic literature search was conducted using the PubMed, Embase, Cochrane Library, clinical trials.gov, China National Knowledge Infrastructure, and WAN FANG databases for re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Bone pain is the most common AE caused by G-CSF and it can be induced by various mechanisms, including inflammatory processes, expansion of the bone marrow, stimulation of osteoclasts and osteoblasts, and afferent nerve stimulation [ 24 ]. According to a systematic review, long-acting G-CSF significantly decreased the rate of bone pain (RR 0.75; 95% CI 0.58–0.98) compared to short-acting G-CSF [ 25 ]. The bone pain events associated with pegfilgrastim were reported 20–45% in RCTs, while 59–71% in post-marketing surveys [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bone pain is the most common AE caused by G-CSF and it can be induced by various mechanisms, including inflammatory processes, expansion of the bone marrow, stimulation of osteoclasts and osteoblasts, and afferent nerve stimulation [ 24 ]. According to a systematic review, long-acting G-CSF significantly decreased the rate of bone pain (RR 0.75; 95% CI 0.58–0.98) compared to short-acting G-CSF [ 25 ]. The bone pain events associated with pegfilgrastim were reported 20–45% in RCTs, while 59–71% in post-marketing surveys [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, besides filgrastim and lenograstim, eight major G-CSF drugs are known: long-acting filgrastim-pegfilgrastim, lipegfilgrastim, mecapefilgrastim [14], empegfilgrastim [15], S/L-G-CSF biosimilar-balugrastim [16], leridistim, pegleridistim [17], and pegteograstim [18].…”
Section: Pharmaceutical Variantsmentioning
confidence: 99%
“…Moreover, the present study further indicated that lung cancer patients who received long-acting rhG-CSF were more likely to develop VTE than those who received short-acting rhG-CSF. Owing to the better therapeutic efficacy of long-acting rhG-CSF in leukocyte boosting than shortacting rhG-CSF (34), long-acting rhG-CSF may correspondingly yield a higher risk of thrombosis due to its greater capacity for the elevation of leukocytes and longer drug maintenance effect.…”
Section: Figurementioning
confidence: 99%